2017
DOI: 10.1136/bmjopen-2017-017030
|View full text |Cite
|
Sign up to set email alerts
|

Economic volatility in childhood and subsequent adolescent mental health problems: a longitudinal population-based study of adolescents

Abstract: ObjectiveThe aim of the current paper was to investigate the association between the patterns of duration, timing and sequencing of exposure to low family income during childhood, and symptoms of mental health problems in adolescence.SettingSurvey administered to a large population-based sample of Norwegian adolescents.ParticipantsSurvey data from 9154 participants of 16–19 years age (53% participation rate; 52.7% girls) were linked to registry-based information about childhood family income from tax return da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 57 publications
(76 reference statements)
4
23
0
1
Order By: Relevance
“…Like previous studies of childhood adversity in population-based samples (Björkenstam et al, 2017;Mersky et al, 2013;Perales et al, 2013;St Clair et al, 2015), although many of our study participants reported low levels of adversity throughout childhood, more than one-third experienced mild levels and about one-sixth were exposed to moderate or higher levels of adversity at some time during childhood. This is consistent with studies of economic trajectories, in which some households move into and out of poverty during childhood (Bøe et al, 2017;Shuey & Willson, 2014), and has also been observed in studies of maltreatment, in which abuse experiences are time-limited for some children (English et al, 2005;Jaffee & Maikovich-Fong, 2011;Manly et al, 2001;Thornberry et al, 2010). However, we did identify small proportions of children who experienced decreasing and increasing adversity throughout childhood, highlighting the clinical and research importance of assessing adversity at multiple times throughout childhood to correctly classify children's adversity experience.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Like previous studies of childhood adversity in population-based samples (Björkenstam et al, 2017;Mersky et al, 2013;Perales et al, 2013;St Clair et al, 2015), although many of our study participants reported low levels of adversity throughout childhood, more than one-third experienced mild levels and about one-sixth were exposed to moderate or higher levels of adversity at some time during childhood. This is consistent with studies of economic trajectories, in which some households move into and out of poverty during childhood (Bøe et al, 2017;Shuey & Willson, 2014), and has also been observed in studies of maltreatment, in which abuse experiences are time-limited for some children (English et al, 2005;Jaffee & Maikovich-Fong, 2011;Manly et al, 2001;Thornberry et al, 2010). However, we did identify small proportions of children who experienced decreasing and increasing adversity throughout childhood, highlighting the clinical and research importance of assessing adversity at multiple times throughout childhood to correctly classify children's adversity experience.…”
Section: Discussionsupporting
confidence: 89%
“…However, we did identify small proportions of children who experienced decreasing and increasing adversity throughout childhood, highlighting the clinical and research importance of assessing adversity at multiple times throughout childhood to correctly classify children's adversity experience. This is consistent with studies of economic trajectories, in which some households move into and out of poverty during childhood (Bøe et al, 2017;Shuey & Willson, 2014), and has also been observed in studies of maltreatment, in which abuse experiences are time-limited for some children (English et al, 2005;Jaffee & Maikovich-Fong, 2011;Manly et al, 2001;Thornberry et al, 2010). may have better accounted for the severity of different types of events.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1), which was conducted between June 2010 and September 2014. Epidemiological studies from Hordaland County have shown similar prevalence and incidence of DM (Joner et al 2004;Stene et al 2004), and similar demographic and income characteristics (Bøe et al 2017), as in other parts of the country. Together with the presence of a national universal healthcare system, this suggests that the study population is representative of the total Norwegian population.…”
Section: Study Design and Patientsmentioning
confidence: 87%